SOMATIC GENE VARIANTS IN NONRESECTABLE CUTANEOUS MELANOMA CELLS AND PHARMACOGENOMIC MARKERS DETECTION: INFLUENCE ON STRATEGY OF EFFECTIVE CANCER TREATMENT - Gulkovskyi, Roman; Kashuba, Vladimir (PH Akademperiodyka, 2026)
The study aimed to identify clinically relevant gene variants in non-resectable cutaneous melanoma samples from Ukrainian patients and to investigate some pharmacogenomic markers using NGS technology to inform cancer treatment strategies. Methods. The study used 30 samples of Ukrainian patients aged 28-76 years, who had nonresectable cutaneous melanomas of various localizations and degrees of differentiation. Ion Torrent NGS technology of targeted gene sequencing (Custom AmpliSeq™ Cancer Hotspot and Pharmacogenomic panels) was used to identify genetic alterations, which were classified by the Franklin by Gennox database and custom pharmacogenomic Ion Reporter Software pipeline. Results. A total of 148 different gene alterations were identified in 40 genes (SNVs, MNVs, INDELs) by the Cancer Hotspot Panel, revealing mutation patterns consistent with international data. However, notable discrepancies exist, such as a high KRAS mutation rate (29.3%), predominantly in stage III tumors, suggesting a role in tumor aggression and progression. We identified frequent TP53 and BRAF mutations, with BRAF V600E being the most common, and observed a higher prevalence of BRAF mutations in females. TP53 mutations are prevalent (59.3%) and vary with age and sex, though their prognostic significance requires further validation. A second key novel finding was the detection of FLT3 mutations in 22.2% of samples, with a statistically significantly higher prevalence in Stage IV disease, suggesting a potential role for FLT3 in melanoma progression and warranting further investigation as a prognostic biomarker and a potential target for existing FLT3 inhibitors. Ultimately, our pilot analysis of pharmacogenomic markers underscores their potential clinical utility in informing personalized treatment decisions. For instance, the identification of a patient with the rs35599367 (G/A) risk allele for adverse drug reactions underscores the value of using pharmacogenetic data to inform the selection between approved therapies. Conclusions. This study reveals unique mutational patterns in the Ukrainian patient cohort, emphasizing the importance of population-specific research to uncover new therapeutic targets and refine personalized treatment strategies. The data suggest that there may be potential for implementing a method of determining both tumor-associated mutations and pharmacogenetic markers of the patient, to facilitate more effective patient treatment. Further validation on a larger number of samples, as well as more exhaustive analysis employing alternative methods, is necessary to substantiate these findings.